Prediction of flooded territories in case of possible breakdown of the sioni earth dam - Gavardashvili, Givi; Ecocenter for Environmental Protection (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"In order to carry out a computer simulation of a flood originating in the case of a possible breakdown of the Sioni earth dam, the author has re-worked the algorithm of the Volna-2”, which allows, in the case of a possible breakdown of the dam, to calculate the wave velocity, the run-out distance according to the topography of river. In the case of a possible breakdown of the Sioni earth dam the population of the Iori valley as well as the areas adjoining the Iori River comes under great flooding. As to the spread of the waters it occurs in the north - eastern and south - western directions."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">In order to carry out a computer simulation of a flood originating in the case of a possible breakdown of the Sioni earth dam, the author has re-worked the algorithm of the Volna-2”, which allows, in the case of a possible breakdown of the dam, to calculate the wave velocity, the run-out distance according to the topography of river. In the case of a possible breakdown of the Sioni earth dam the population of the Iori valley as well as the areas adjoining the Iori River comes under great flooding. As to the spread of the waters it occurs in the north - eastern and south - western directions.